The paradoxical effects of workforce shortages on rural interprofessional practice. Issue 1 (21st March 2014) - McNeil, Karen; Mitchell, Rebecca; Parker, Vicki
<x xml:space="preserve">Abstract</x> Rationale and Aim While interprofessional practice has been promoted as a solution to the challenges besetting rural health services, current evidence does not offer a clear explanation as to why it is effective in some domains and yet is not successful in others. At the same time, rural clinicians are frequently faced with major workforce pressures and this has a significant influence on professional practice. The aim of this study was to explore how these pressures impact on rural interprofessional practice. Method This study is part of a larger project investigating factors that enhance and detract from effective interprofessional working. We utilised a modified realistic evaluation approach to analyse the context, mechanisms and outcomes of rural interprofessional practice. Approval for this study was granted by an accredited research ethics committee. Semi‐structured interviews were conducted with 22 rural clinicians who were purposively recruited from a range of settings, roles, locations and professions. Findings and Discussion We found that clinicians often invested in interprofessional practice because of the need to manage intense workloads and this necessitated sharing of responsibilities across disciplines and blurring of role boundaries. Paradoxically, participants noted that workload pressures hampered interprofessional working if there were long‐term skill shortages. Sharing workload and responsibility is an important motivator for rural practitioners to engage in interprofessional practice; however, this driver is only effective under circumstances where there are sufficient resources to facilitate collaboration. In the context of intransient resource challenges, rural health service managers would be best to focus on enabling IPP through facilitating role understanding and respect between clinicians. This is most feasible via informal workplace learning and allowing time for teams to reflect on collaborative processes.